Digital Learning Factory for Developing Soft Skills and Scientific Creativity of Prospective Science Teachers toward SDG 4 - Dwi Pangga; Made Hery Santosa; I Wayan Widiana; Ketut Suma; Wayan Suastra; Putu Artawan (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to analyze the urgency of implementing the Learning Factory (LF) model in developing soft skills and scientific creativity in prospective science teachers at the Faculty of Science, Engineering, and Applied Sciences (FSTT) of Mandalika University of Education. This study also aims to identify the gap between the competencies acquired during education and the needs of the world of work in the era of the Industrial Revolution 4.0. Method: This study uses a survey approach through a tracer study involving alumni of the Physics Education, Chemistry Education, Biology Education, and Mathematics Education study programs at FSTT Undikma. Data were collected through questionnaires to determine the relevance of graduates' competencies to the needs of the world of work, then analyzed descriptively. Results: The results showed that most alumni were able to find employment relatively quickly after graduation. However, some alumni felt that the jobs they obtained were not fully in line with their field of study. This indicates a gap between higher education competencies and the needs of the world of work. The Learning Factory model, which is based on project-based learning and industrial experience, has the potential to improve technical skills while strengthening students' collaboration, communication, and innovation abilities. Novelty: This study highlights the importance of integrating the Learning Factory model with the Outcome-Based Education (OBE) approach to improve graduate employability through the development of more holistic competencies that are relevant to the needs of the world of work.